Sustainable Mangrove Management As An Effort to Achieve the Sustainable Development Goals in Donggala Regency - Muthia Muthia; Riyadi Slamet; Mustainah Mustainah; Pageno Isbon; Irfan Mufti (Jurnal Penelitian Pendidikan IPA, 2025)
This study addresses ineffective implementation of sustainable mangrove management policies in Donggala Regency in relation to achieving the Sustainable Development Goals (SDGs). The study aims to analyze policy implementation and identify key factors influencing sustainable mangrove governance. A descriptive qualitative approach was employed, with data collected through in-depth interviews, observation, documentation, and literature review. Informants were purposively selected from local government institutions, coastal communities, and environmental organizations. Data analysis used Malcolm L. Goggin et al.’s (1990) policy implementation framework, focusing on policy content, communication structure, and the reputation of implementing actors. The findings indicate that while policy substance is relatively adequate, weaknesses in communication and limited government credibility impede effective implementation, resulting in a greater operational role for local communities and non-governmental organizations. The study concludes that strengthening multi-actor collaboration is crucial for improving sustainable mangrove management and supporting SDG achievement